2017
DOI: 10.18203/2349-3291.ijcp20170701
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors in children with birth asphyxia

Abstract: INTRODUCTIONWorld Health Organisation (WHO) defines Birth asphyxia as failure to initiate and sustain breath-ing in a newborn at birth. 1 It is a temporary interruption of oxygen availability that implies a risky metabolic challenge, even when the insult does not lead to a fatal outcome. Asphyxia results in hypoxemia (lack of oxygen) and hypercapnia (accumulation of carbon diox-ide).The combination of the decrease in oxygen supply (hypoxia) and blood supply (ischemia) re-sults in a ABSTRACT Background: Birth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 6 publications
23
27
0
Order By: Relevance
“…This finding is comparable to studies conducted at Acharya Vinobha Bhave rural hospital in India, Pakistan tertiary hospital in Karachi, Mululago hospital in Uganda, and Phramongkutklao hospital in Thailand. 7,13,15,17,21 This might be attributable to the fact that the non-vertex presentation had an increased risk of umbilical cord prolapse, head entrapment and birth injury which result in oxygen deprivation. 22 In our research, neonates entangled in the cord are 5.67 times more likely to develop asphyxia than those not entangled in the cord.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable to studies conducted at Acharya Vinobha Bhave rural hospital in India, Pakistan tertiary hospital in Karachi, Mululago hospital in Uganda, and Phramongkutklao hospital in Thailand. 7,13,15,17,21 This might be attributable to the fact that the non-vertex presentation had an increased risk of umbilical cord prolapse, head entrapment and birth injury which result in oxygen deprivation. 22 In our research, neonates entangled in the cord are 5.67 times more likely to develop asphyxia than those not entangled in the cord.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated that preterm birth is one of the main risk factors associated with perinatal asphyxia (Yadav & Damke, 2017, Pitsawong, 2011, Ilah et al, 2015 probably due to the immaturity of the newborn preterm infants' pulmonary system, leading to respiratory failure (Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Antepartum risk factors include severe maternal hypertensive diseases during pregnancy [12,13], antepartum haemorrhage [14,15], history of still birth [16], antenatal care visits [13,14,16], oligohydramnios [13], maternal fever [12, -14, 17] and maternal anaemia [12,13,16,16], young maternal age [12,17,18], advanced maternal age [19], and low educational status (illiterate and primary education level) [16,18]. Intrapartum risk factors include malpresentation [12-14, 16, 20], prolonged second stage of labour [14,15,21], home delivery [12,17], obstructed labour [12,17,22], oxytocin use [14], and meconium stained amniotic fluid [12, 13, 16 , 17].…”
Section: Introductionmentioning
confidence: 99%